Ebselen and diphenyl diselenide against fungal pathogens: A systematic review. (9th January 2021) - Benelli, Jéssica Louise; Poester, Vanice Rodrigues; Munhoz, Lívia Silveira; Melo, Aryse Martins; Trápaga, Mariana Rodrigues; Stevens, David A; Xavier, Melissa Orzechowski
Abstract: Fungal infections are one of the most prevalent diseases in the world and there is a lack of new antifungal drug development for these diseases. We conducted a systematic review of the literature regarding the in vitro antifungal activity of the organoselenium compounds ebselen (Eb) and diphenyl diselenide [(PhSe)2 ]. A systematic review was carried out based on the search for articles with data concerning Minimal Inhibitory Concentration (MIC) values, indexed in international databases and published until August 2020. A total of 2337 articles were found, and, according to the inclusion and exclusion criteria used, 22 articles were included in the study. Inhibitory activity against 96% (200/208) and 95% (312/328) of the pathogenic fungi tested was described for Eb and [(PhSe)2 ], respectively. Including in these 536 fungal isolates tested, organoselenium activity was highlighted against Candida spp., Cryptococcus ssp., Trichosporon spp., Aspergillus spp., Fusarium spp., Pythium spp., and Sporothrix spp., with MIC values lower than 64 μg/mL. In conclusion, Eb and [(PhSe)2 ] have a broad spectrum of in vitro inhibitory antifungal activity. These data added with other pharmacological properties of these organoselenium compounds suggest that both compounds are potential future antifungal drugs. Whether MICs toward the upper end of the ranges described here are compatible with efficacious therapy, and whether they may achieve such end as a result of the favorable non-antimicrobial effects of selenium on the host, requires more in vivo testing. Lay Summary: Fungal infections require the investigation of new drugs. The study is a systematic review of organo-selenium compounds with potential antifungal action. In 22 articles included in this review, in a total of 536 isolates of pathogenic fungi tested, the compounds showed action in more than 90% of them.